Freedom in the Arab world concepts and ideologies in Arabic thought in the nineteenth century - Abu-'Uksa, Wael 1979- (Cambridge University Press, 2016)
A preoccupation with the subject of 'freedom' is a core issue in the construction of all modern political ideologies. Wael Abu-'Uksa examines the development of the concept of freedom in nineteenth-century Arabic thought, its ideological offshoots, and their substance as they developed within the context of a changing Middle East